Gas Chromatographic Determination of Benzyl Alcohol in Midazolam Injection - Patil, Dhanaji; Mangaonkar, Kiran; Lokhande, R.S.; Wabgaonkar, Swati (Asian Journal of Chemistry, 2010)
A simple, fast and accurate gas chromatographic method has been developed for the determination of benzyl alcohol content in midazolam injection. The analysis was carried out on Shimadzu 17A. The column used was 5% carbowax on Chromsorb HP (2 m, 3.6 mm id). The detector used was flame ionization detector. The validation of the proposed method was also carried out.